Determinants of parental seasonal influenza vaccine hesitancy in the Eastern Mediterranean region: A cross-sectional study - Fadl, Noha; Al Awaidy, Salah T.; Elshabrawy, Abdelhamid; Makhlouf, Mona Sayed Aly Hassan; Ibrahim, Sarah Assem; Abdel-Rahman, Suzan; Tookhy, Nazir Ahmad; Alsalmani, Abdullah; Al-Saeedi, Mays; Al-Sawalha, Ibrahim; El-Din, Mohammad Amin Aly; Saad, Janet; et al. (Frontiers in Public Health, 2023)
Background: The influenza vaccine can reduce the risk of influenza-associated hospitalizations and deaths among children. Given that parents are children's primary decision makers, this study examined parental influenza vaccine hesitancy (VH) towards childhood influenza vaccine and its determinants in the Eastern Mediterranean region (EMR). Methods: A cross-sectional study was conducted using an anonymous online survey in 14 EMR countries. Parents of children aged 6 months to 18 years were included. The Parent Attitude about Childhood vaccines (PACV) was used to assess VH. Chi square test and independent t-test were used to test for association in qualitative and quantitative variables, respectively. A structural equations model (SEM) was used to identify direct and indirect determinants of VH. Results: Nearly half of the parents were hesitant about vaccinating their children against influenza (50.8%). Parental VH was significantly greater among older age mothers (37.06±8.8 years, p=0.006), rural residents (53.6%, p<0.001), high income countries residents (50.6%, p<0.001), and mothers with higher educational levels (52.1%, p<0.001). Parents of school-aged children (5-9 years) (55.6%, p<0.001), children free from any comorbidities (52.5%, p<0.001), children not getting routine vaccination at all (51.5%, p=0.03), children not vaccinated against COVID-19 (54.3%, p<0.001), in addition to parents who were not vaccinated against influenza (57.1%, p<0.001) were significantly associated with increased likelihood of VH. The SEM suggests that mother's age, residence, country income, child gender, total number of children and source of information regarding influenza vaccine had a direct effect on VH. Meanwhile, parents vaccinated against influenza, children completely or partially vaccinated with routine vaccines and children vaccinated against COVID-19 had indirect effect on VH. Conclusion: Nearly half of the parents were hesitant about vaccinating their children against influenza. Understanding parental attitudes towards their children’s vaccination is critical to develop and implement interventions to address VH and improve vaccine uptake.